A community-based intervention for improving utilization of medical services by rape survivors in refugee camps in Zambia (2019)
Background: Rape is the most common form of violence in conflict and refugee situations but because of the associated stigma few cases are reported. This study assessed the outcome of an intervention targeted at women groups on the utilization of medical services by rape survivors in refugee camps in Zambia. Methods: A prospective quasi-experimental community-based intervention study was carried out in two refugee camps allocated into intervention and comparison areas. The intervention was participatory education sessions for women groups. Data was collected using the clinic records and the main outcome was the number of rape survivors who utilized and completed medical services provided at the camp clinics. Univariate, bivariate and multivariate analyses were carried out with level of significance set at 5%. Results: The proportion of the rape survivors who accessed medical care within 72 hours increased significantly from 41.2% to 84.8% in the intervention area but from 31.1% to 38.9% in the comparison area, (p=0.005). Those who completed their medical treatment and the follow-up visits increased significantly from 42.8% to 94.8% in intervention area but reduced from 38.5% to 21.4% in the comparison area, (p=0.002). Being resident in the intervention area predicted the utilization of medical services, [OR: 3.15; 95%CI: 1.955-5.681], p=0.002. Conclusion: Community-based intervention using participatory women’s group discussion had a significant impact on increasing the utilization of medical services by rape survivors and should be considered for scaling up as a key intervention for increasing utilization of medical services for rape survivors especially in refugee situations.